Boceprevir and telaprevir for the treatment of chronic hepatitis C genotype 1 infection: an indirect comparison meta-analysis - Cooper CL; Druyts E; Thorlund K; Nachega JB; El Khoury AC; O'Regan C; Mills EJ (Dove Medical Press, 2012)
Curtis L Cooper1, Eric Druyts2, Kristian Thorlund3, Jean B Nachega4, Antoine C El Khoury5, Christopher O'Regan6, Edward J Mills2,31Division of Infectious Diseases, Faculty of Medicine, 2Faculty of Health Sciences, University of Ottawa, Ottawa, 3Department of Clinical Epidemiology and Biostatistics, McMaster University, Hamilton, Ontario, Canada; 4Bloomberg School of Public Health, Johns Hopkins University, Baltimore, MD, 5Merck and Co, Inc, Whitehouse Station, NJ, 6Merck Sharp and Dohme Ltd, Hoddesdon, Hertfordshire, United KingdomBackground: The aim of this study was to examine the relative efficacy and safety of boceprevir and telaprevir, when used in combination with pegylated interferon alpha and ribavirin, using an indirect comparison meta-analysis.Methods: Published phase II and phase III randomized placebo-controlled trials examining the efficacy of boceprevir and telaprevir in chronic hepatitis C virus genotype 1 infected adult populations were included. The primary outcomes were sustained virologic response, relapse, and discontinuation of all study drugs. Secondary outcomes included the adverse events of anemia, neutropenia, rash, and pruritus. Results: Four boceprevir trials and six telaprevir trials were included. No significant differences were observed for sustained virologic response among either naïve (relative risk [RR] 1.14, 95% confidence interval [CI] 0.93–1.37, P = 0.20) or experienced patients (RR 0.81, 95% CI 0.52–1.23, P = 0.30). Similarly, for relapse among naïve (RR 0.80, 95% CI 0.18–3.45, P = 0.77) and experienced patients (RR 1.71, 95% CI 0.90–3.24, P = 0.10), or discontinuation of therapy for naïve (RR 0.80, 95% CI 0.28–2.29, P = 0.72) and experienced patients (RR 0.88, 95% CI 0.69–1.12, P = 0.30). Telaprevir was more likely to be associated with rash and pruritus, and boceprevir was more likely to be associated with neutropenia in certain patient populations.Conclusion: Boceprevir and telaprevir appear comparable in terms of sustained virologic response, relapse, or discontinuation of therapy for patients treated with standard-dose therapy durations and response-guided therapy durations.Keywords: direct-acting antivirals, boceprevir, telaprevir, hepatitis C, meta-analysis